2012
DOI: 10.1186/2190-4715-24-7
|View full text |Cite
|
Sign up to set email alerts
|

Levels and trends of industrial chemicals (PCBs, PFCs, PBDEs) in archived herring gull eggs from German coastal regions

Abstract: Background: Polychlorinated biphenyls [PCBs], perfluorinated compounds, and polybrominated diphenyl ethers [PBDEs] were retrospectively analyzed in archived herring gull (Larus argentatus) eggs from the North and the Baltic Sea over the last 20 years. The aim was to assess temporal trends and effects of regulatory measures. Results: PCBs (sum of 7 congeners) were highest in eggs from the North Sea island Trischen, i.e., 3,710 to 20,760 ng/g lipid weight [lw] compared to 2,530 to 11,650 ng/g lw on the North Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 78 publications
3
27
0
Order By: Relevance
“…Interestingly, when we compared these with our statistical analyses (Additional file 7, Figures S8-S10) we found 11 datasets showing clearly diverging results (tawny owl [11], polar bear (Ittoqqortoormiit) [124], beluga (Cook Inlet) [123], polar bear (Barrow) [132], herring [139], eel (Haringvliet East, Lobith [107]), herring gull (Heuwiese [80], Mellum-3 sets [80,105,128]). In eight cases, our statistical analyses resulted in insignificant trends, with low power to detect a trend, whereas the authors found significantly decreasing trends in seven (tawny owl [11], eel (Haringvliet East, Lobith [107]), herring gull (Heuwiese [80]), herring gull (Mellum-3 datasets [80,105,128]) and significantly increasing trends in one of these datasets (polar bear, Barrow [132]). For one dataset (polar bear (Ittoqqortoormiit [124]), our results showed no significant trends on either side of the change point but statistically significantly higher concentrations after the change point, whereas the authors found a significant increasing trend before the change point and significant decreasing trend after.…”
Section: Biological Samplesmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, when we compared these with our statistical analyses (Additional file 7, Figures S8-S10) we found 11 datasets showing clearly diverging results (tawny owl [11], polar bear (Ittoqqortoormiit) [124], beluga (Cook Inlet) [123], polar bear (Barrow) [132], herring [139], eel (Haringvliet East, Lobith [107]), herring gull (Heuwiese [80], Mellum-3 sets [80,105,128]). In eight cases, our statistical analyses resulted in insignificant trends, with low power to detect a trend, whereas the authors found significantly decreasing trends in seven (tawny owl [11], eel (Haringvliet East, Lobith [107]), herring gull (Heuwiese [80]), herring gull (Mellum-3 datasets [80,105,128]) and significantly increasing trends in one of these datasets (polar bear, Barrow [132]). For one dataset (polar bear (Ittoqqortoormiit [124]), our results showed no significant trends on either side of the change point but statistically significantly higher concentrations after the change point, whereas the authors found a significant increasing trend before the change point and significant decreasing trend after.…”
Section: Biological Samplesmentioning
confidence: 99%
“…Within the group of 13 studies exhibiting change points, seven studies showed decreasing concentrations after the change point (roe deer [79], polar bear liver [134], herring gull eggs (Trischen) [80], northern sea otter [42], beluga whale [123], eelpout [128], and herring [139]). Four studies exhibited insignificant change both prior and post change point (polar bear [124], grey seal [106], herring gull eggs (Mellum) [80], guillemot eggs [94]). However, in three of these four studies, the concentrations after the change point were significantly higher than before the change point (stepwise increase rather than a continuous increase).…”
Section: Biological Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…PBDEs are highly persistent and bioaccumulative, which make them potentially dangerous to humans and perturbing to ecosystems (Birnbaum and Staskal, 2004). Such environmental concern has resulted in the cessation or discontinuance of the production of PBDEs in most countries in the recent years (Fliedner et al, 2012).…”
Section: Introductionmentioning
confidence: 99%